Incidence of and risk factors for late cholecystectomy in survivors of childhood cancer: A report from the Childhood Cancer Survivor Study. (July 2020) - Dieffenbach, Bryan V.; Li, Nan; Madenci, Arin L.; Murphy, Andrew J.; Barnea, Dana; Gibson, Todd M.; Tonorezos, Emily S.; Leisenring, Wendy M.; Howell, Rebecca M.; Diller, Lisa R.; Liu, Qi; Chow, Eric J.; et al.
Abstract: Background: Gallbladder disease and need for cholecystectomy are common and significant contributors to patient morbidity and healthcare costs. Childhood cancer survivors are at elevated risk for developing cholelithiasis. However, their incidence of and risk factors for late (>5 years from diagnosis) cholecystectomy have not been studied. Methods: A total of 25, 549 survivors (median age at diagnosis 6.9 years, range 0–21.0; current age 30.7 years, range 5.6–65.9) diagnosed between 1970 and 1999 and 5037 siblings were queried for self-reported cholecystectomy occurring five or more years from primary cancer diagnosis. Piecewise exponential models evaluated associations between cancer treatment exposures and late cholecystectomy. Results: Over a median follow-up period of 21.9 and 26.0 years, respectively, 789 survivors and 168 siblings underwent late cholecystectomy (cumulative incidence 7.2%, 95% confidence interval [CI] = 6.5–7.8% and 6.6%, 95% CI = 5.4–7.6%, respectively; rate ratio [RR] = 1.3, 95% CI = 1.1–1.5). Compared with siblings, survivors of acute lymphoblastic leukaemia (RR = 1.4, 95% CI = 1.2–1.8), soft tissue sarcoma (RR = 1.4, 95% CI = 1.0–1.8) and bone cancer (RR = 1.3, 95% CI = 1.0–1.8) were at the greatest risk. In addition to attained age, female sex and increasing body mass index, exposure to high-dose (≥750 mg/m 2 ) platinum chemotherapy (RR = 2.6, 95% CI = 1.5–4.5), vinca alkaloid chemotherapy (RR = 1.4, 95% CI = 1.1–1.8) or total body irradiation (TBI; RR = 2.2, 95% CI = 1.2–4.2) were each associated with late cholecystectomy. Conclusions: Independent of traditional risk factors for gallbladder disease, exposure to high-dose platinum chemotherapy, vinca alkaloid chemotherapy or TBI increased risk for late cholecystectomy. These findings should inform current long-term follow-up guidelines and education regarding risk for late cholecystectomy. Highlights: Cholecystectomy rates are 30% higher in childhood cancer survivors than in siblings. High-dose platinum agents, vinca alkaloids and TBI increase risk for cholecystectomy. These agents confer increased risk in survivors without classical risk factors. These data will inform long-term follow-up guidelines for survivors.